Last chance for life clemency in southeast Asian death penalty cases - Pascoe, Daniel 1983- (Clarendon studies in criminology., 2019)
"All five contemporary practitioners of the death penalty in the Association of Southeast Asian Nations (ASEAN), Indonesia, Malaysia, Thailand, Singapore and Vietnam, have performed executions on a regular basis over the past few decades. NGO Amnesty International currently classifies each of these nations as death penalty 'retentionists'. However, notwithstanding a common willingness to execute, the number of death sentences passed by courts that are reduced to a term of imprisonment or where the prisoner is released from custody altogether, through grants of clemency by the executive branch of government, varies remarkably among these neighbouring political allies. In Last Chance for Life: Clemency in Southeast Asian Death Penalty Cases, the patterns which explain why some countries in the region award clemency far more often than do others in death penalty cases are explored and explained. Over the period under analysis from 1991 to 2016, the regional outliers were Thailand (with more than 95% of condemned prisoners receiving clemency after exhausting judicial appeals) and Singapore (with fewer than 1% of condemned prisoners receiving clemency).Malaysia, Indonesia and Vietnam fall at points in between these two extremes. What results is the first research monograph, anywhere in the world, to compare death penalty clemency across national borders using empirical methodology, the latter a systematic collection of clemency data in multiple jurisdictions using archival and 'elite' interview sources. Last Chance for Life: Clemency in Southeast Asian Death Penalty Cases is an authoritative resource for legal practitioners, criminal justice policy makers, scholars and activists throughout the ASEAN region and around the world"--Provided by publisher.